Writing to clients and referring professionals about psychological assessment results : a handbook of style and grammar - Allyn, J. B. (Janet B.); Finn, Stephen E.; Fischer, Constance T. (New York : Routledge, 2012)
'This book represents a natural evolution from the author's work with editing assessment reports and is specifically structured to meet the writing and communicating needs of the psychologist assessor. A combination of reference book and tutorial, Writing to Clients elucidates the qualities that create a writer's unique presence on the page with illustrations of correct English grammar, and is appropriate for graduate psychology students and for practicing professionals. In addition to style and grammar, the author details how to write less formal reports in letter form and to write a therapeutic story as an extension of the report for child, teenager, or adult'--
Includes bibliographical references : (p. 213-219) and index.
Keywords: Psychology -- Methodology; Behavioral assessment; Psychodiagnostics; Report writing; English language -- Writing